Patagonia, de margen exótico a periferia turística. Una mirada sobre un área natural protegida de frontera - Paula Gabriela Núñez; Brenda Matossian; Laila Vejsbjerg (PASOS Revista de Turismo y Patrimonio Cultural, 2012)
During the first half of the twentieth century, National Parks in Argentina were located in peripheral border spaces. This configuration responded to previous territorial organization logics developed in the country. In order to analyze the impact and influence of these Natural Protected Areas, the Nahuel Huapi National Park (Andean Patagonia, Argentina) case study was considered. It was concluded that, in the region of the Nahuel Huapi, the centralization in the national territorial administration was consolidated through the institutionalization of a Natural Protected Area. Moreover, this process allowed the identification of different approaches from which local planning development and tourism were thought over time, affecting the way Natural Protected Areas were conceived.